Survival global politics and strategy
Survival , the Institute's bi-monthly journal, is a leading forum for analysis and debate of international and strategic affairs. With a diverse range of authors, thoughtful reviews and review essays, Survival is scholarly in depth while vivid, well-written and policy-relevant in approach. Shaped by its editors to be both timely and forward-thinking, the journal encourages writers to challenge conventional wisdom and bring fresh, often controversial, perspectives to bear on the strategic issues of the moment. Survival is essential reading for practitioners, analysts, teachers and followers of international affairs. Each issue also contains Book Reviews of the most important recent publications on international politics and security.